Competition Policy and Regulation in Ports and Shipping - Gilberto M. Llanto; Leilanie Q. Basilio; Enrico L. Basilio (Philippine Institute for Development Studies (PIDS), 2005)
The Philippines is an archipelago of approximately 7,107 islands. It has a long coastline extending to 235,973 square kilometers which is longer than that of the United States (UNESCAP 2002b). The countrys archipelagic configuration requires an efficient maritime transport infrastructure composed of ports and shipping for growth and socioeconomic integration. The integration of peripheral islands to the urban economic nodes such as Metro Manila, Cebu, Davao and General Santos and the diffusion of investments and economic activities fundamentally count on an efficient road and maritime transport network. This paper examines competition policy and the regulatory framework of the port and shipping sectors. It assesses the policies and programs of the government in promoting competition in these sectors and recommends areas for policy and regulatory reform. After a brief description of the analytical underpinnings of competition policy and regulation the paper reviews the present state of competition and regulation in Philippine ports and inter-island shipping to identify emerging issues that call for policy action. It provides specific recommendations for policy and regulatory reform.
Keywords: 330; competition policy; regulatory framework; maritime transport; ports and inter-island shipping; market contestability; landlord port model; Wettbewerbspolitik; Reform; Regulierung; Hafenwirtschaft; Frachtschifffahrt; Philippinen